The Impact of Awareness and Training on Enterprise Risk Management: A Case Study on Enhancing the Role of Training and Raising Awareness in Improving the Efficiency of Risk Management in Industrial Companies and Government Institutions in Jubail Industrial City, Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to explore the impact of awareness and training on the efficiency of risk management in industrial companies and governmental institutions in Jubail Industrial City, Saudi Arabia. A descriptive-analytical methodology was used to collect data through questionnaires distributed to a sample of employees, in addition to conducting interviews with several officials and experts in the field of risk management. The results showed that awareness and training play a crucial role in improving the efficiency of risk management. The data indicated that the majority of participants received awareness and training programs, which significantly improved their ability to identify and assess risks, and take necessary preventive measures. The results also showed that combining awareness and training enhances organizational performance and reduces the number of accidents and risks. Data analysis indicated variability in the level of awareness and training among employees, highlighting the need to enhance these programs to be more comprehensive and continuous. The study emphasized the importance of integrating awareness and training to ensure a greater impact on the efficiency of risk management. In light of these findings, the study recommended the need to enhance awareness and training programs in industrial companies and governmental institutions in Jubail, and update them periodically to keep pace with the latest developments. It also called for adopting an integrated approach that combines awareness and training to improve organizational performance and enhance risk management efficiency. This study provides a significant contribution to understanding how to improve risk management through awareness and training, offering practical recommendations that can help institutions in Jubail effectively face challenges and risks, thereby enhancing their ability to achieve organizational sustainability.
Keywords: Awareness; Training; Risk Management; Industrial Companies; Government Institutions